THE RELATIONSHIP BETWEEN TEACHER SELF-ESTEEM AND SELF-ACTUALIZATION IN SCHOOLS’ LEARNING COMMUNITY DURING THE IMPLEMENTATION OF KURIKULUM MERDEKA - Rismawati; Cut Mutia (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The learning process is something that cannot be separated from a teacher's life. Teachers are expected to be able to develop all the potential and talents they have as a form of self-actualization. However, there are still teachers found to be passive in the learning community. The purpose of this research is to determine the relationship between teacher self-esteem and self-actualization ability in a learning community in the implementation of the Merdeka Curriculum in the Southwest Aceh District. The research used a correlational study design with a cross-sectional study approach (α=0.05). The respondents amounted to 103 individuals, selected using the total sampling technique. The instruments used were a self-esteem questionnaire (Rosenberg Self-esteem) with 10 statement items and a self-actualization questionnaire (Peak Experiences Self-Actualization) with 28 statement items. Data analysis was conducted using univariate and bivariate analysis (Spearman Rank Correlation test). The research results found the mean self-esteem score to be 19.89, a standard deviation of 3.346, and a self-esteem score range of 11-29. As for self-actualization, low self-actualization (28.2%), approaching self-actualization (25.2%), moderate self-actualization (28.2%), and high self-actualization (18.4%) were obtained. There is a strong relationship between teacher self-esteem and self-actualization ability in the learning community in the implementation of the Merdeka Curriculum (p=0.000, r= +0.633). The results of this research indicate that the learning community can influence teacher self-esteem to sharpen and achieve self-actualization.